High purity syngas and hydrogen coproduction using copper-iron oxygen carriers in chemical looping reforming process. (1st February 2019) - Nadgouda, Sourabh G.; Guo, Mengqing; Tong, Andrew; Fan, L.-S.
Highlights: Cu-Fe oxygen carriers investigated for syngas and hydrogen coproduction. Simulated co-current moving bed reactor: 99.5% CH4 conversion, 97.5% syngas purity. >99.9% H2 purity during 5 redox cycles in a fixed bed reactor. Net H2 production: 28% higher than autothermal reforming baseline case. Effective thermal efficiency: 10% higher than autothermal reforming baseline case. Abstract: Chemical looping reforming presents an attractive alternative to the conventional processes for chemicals and energy production from carbonaceous fuels with significant reduction in carbon emissions and high exergy efficiency. Production of syngas and hydrogen is important because the former is a critical building block for valuable chemicals and latter is a source of clean energy. The use of copper-iron (Cu-Fe) oxygen carriers for coproducing syngas and hydrogen in a chemical looping reforming process is studied via experiments and process simulations. Three different compositions of Cu and Fe oxides are examined for their properties concerning the reactivity towards fuel and the selectivity towards syngas. The feasibility of using a co-current moving bed reactor configuration for syngas production is probed experimentally in a fixed bed reactor by placing the fully oxidized and reduced oxygen carrier in series. The methane conversion and dry syngas purity as high as 99.5% and 97.5%, respectively, are observed for copper oxide (20 wt%) - iron oxide (60 wt%) - aluminium oxide (20 wt%) oxygen carrier in a simulated co-current moving bed reactor. Key performance parameters including effective thermal efficiency for 5 different configurations of the chemical looping reforming process from ASPEN Plus simulation software are compared against the baseline case of the auto-thermal reforming process. Apart from an improvement in the natural gas conversion and syngas purity in the chemical looping reforming process, the net hydrogen production is increased by 28% and effective thermal efficiency is increased by 10% over that of the auto-thermal reforming process.